Redox Homeostasis and Prospects for Therapeutic Targeting in Neurodegenerative Disorders. (3rd August 2021) - Akanji, Musbau Adewumi; Rotimi, Damilare Emmanuel; Elebiyo, Tobiloba Christiana; Awakan, Oluwakemi Josephine; Adeyemi, Oluyomi Stephen
Abstract : Reactive species, such as those of oxygen, nitrogen, and sulfur, are considered part of normal cellular metabolism and play significant roles that can impact several signaling processes in ways that lead to either cellular sustenance, protection, or damage. Cellular redox processes involve a balance in the production of reactive species (RS) and their removal because redox imbalance may facilitate oxidative damage. Physiologically, redox homeostasis is essential for the maintenance of many cellular processes. RS may serve as signaling molecules or cause oxidative cellular damage depending on the delicate equilibrium between RS production and their efficient removal through the use of enzymatic or nonenzymatic cellular mechanisms. Moreover, accumulating evidence suggests that redox imbalance plays a significant role in the progression of several neurodegenerative diseases. For example, studies have shown that redox imbalance in the brain mediates neurodegeneration and alters normal cytoprotective responses to stress. Therefore, this review describes redox homeostasis in neurodegenerative diseases with a focus on Alzheimer's and Parkinson's disease. A clearer understanding of the redox-regulated processes in neurodegenerative disorders may afford opportunities for newer therapeutic strategies.